HIV/TB co-infection in the North-West Region of Russia - Z. M. Zagdyn; V. B. Galkin; G. S. Balasanyants (Журнал инфектологии, 2014)
With the aim to assess the HIV/TB epidemic situation and its features in the different areas of the North-West Federal Region statistical data during the last five years (2008–2012) were analyzed. In the study we used information of HIV-infection, tuberculosis and their combination from the annual reporting forms. The study found that in the North-West Federal Region in the recent years the number of HIV/TB co-infected patients is increased steadily the majority of whom is revealed in the penitentiary system. Lethal outcomes in HIV/TB co-infected patients are higher than in HIV-seropositive subjects without TB. Also reporting data from several areas have not been valid enough and could lead to distorted assessment of the real epidemic situation. Thus obtained results can contribute to providing appropriate measures to stabilize the HIV, as well as the TB and HIV/TB epidemic situation, enhance TB prevention, expand TB finding methods and improve TB treatment approaches in HIV/TB co-infected patients in the North-West Region of Russia.